A Study of z-Magnitude Dependence in the Spatial Orientation of Angular Momentum Vectors of Galaxies having Redshift < 30,000 km s-1 - Yadav, Shiv Narayan (Tribhuvan University Journal, 2016)
I present a study of spin vector orientations of 229,675 z-magnitude SDSS (Sloan Digital Sky Survey) galaxies having red shift of 0.05 to 0.10. The z-magnitudes are observed through 913.3 nm CCD (charge coupled device) filter attached to SDSS telescope located at New Mexico, USA. We have converted two dimensional data to three-dimensional by Godlowskian Transformation. Our aim is to find out non-random effects in the spatial orientation of galaxies. The expected isotropy distribution curves are obtained by removing the selection effects and performing a random simulation method. In general, spinvector orientations of galaxies are found to be random, supporting Hierarchy model of galaxy formation. In some samples (z12 and z13) of polar angle distribution is observed anisotropy supporting Primordial Vorticity Theory. For azimuthal angle distribution in more sample we observed anisotropy result. A local anisotropy is observed in few samples suggesting a gravitational tidal interaction, merging process and gravitational lensing effect.